'Le Pavé Rouge': Making an Example of John Singer Sargent. Issue 1 (2nd January 2018) - Viraben, Hadrien
Abstract : 'Le Pavé Rouge' is the ironic title given by Robert de Montesquiou to a monographic article he devoted to John Singer Sargent in France in 1905. Within a frank condemnation of the American painter, the aesthete wove around Sargent's name a complex network of his own personal enemies (artists, writers, collectors) as other targets of his article. This article tries to establish how Montesquiou reinvested his own ambitions in a declaration of war. The aim is to show how Sargent becomes a strategic issue for Montesquiou's agenda as an art critic, writer and pre-eminent figure of 'le Tout-Paris'.